EPISTEMOLOGI IBNU RUSYD DALAM MEREKONSILIASI AGAMA DAN FILSAFAT (Ibn Rushd's Epistemology in The Reconciliation of Religion and Philosophy) - Hamzah Hamzah; Wa Muna Wa Muna (IAIN Kendari, 2018)
In the history of Islamic thought, revelation and ratios are two issues that have become endless debates in relation to religion and philosophy. This problem raises two different views, namely the stronghold of thought which prioritizes revelation and overrides ratios, and the stronghold of thought which prioritizes ratios and denies revelation.The issue has become a polemic in religious and philosophical thinking, often causing victims to be subject to fierce opposition in the two extremes of opinion that differ in views. One proof of the fierce opposition between the two stronghold of thought is the kufr verdict given by Al-Gazali (1058-1111 AD) to Muslim philosophers, such as Al-Farabi (870-950 AD) and Ibn Sina (980-1037 AD). Even, Ibn Rushd (1126-1198 AD) himself had felt the punishment of exile and burning of philosophical books in his time. Therefore, Ibn Rushd sought to find a reconciliation point between revelation and ratio in relation to religion and philosophy. However, Ibn Rushd was not the first philosopher try to reconcile these two things, previously there were philosophers Al-Kindi (801-876 AD), Al-Farabi (870-950 AD), Al-Sijitsani (d. 1000 AD), Ibn Miskawaih (941-1030 AD), Ibn Sina (980-1037 AD) and Ibn Tufail (1110-1184 AD). Ibn Rushd's effort in reconciling religion and philosophy was written in his book entitled Fashl al-Maqal wa Taqrir ma Bain al-Hikmah wa al- Syari’ah min al-Ittishal. In the reconciliation effort, he used qiyas syar'i and ta’wil.